Scaffold-Free Tubular Tissues Created by a Bio-3D Printer Undergo Remodeling and Endothelialization when Implanted in Rat Aortae - Itoh, Manabu; Nakayama, Koichi; Noguchi, Ryo; Kamohara, Keiji; Furukawa, Kojirou; Uchihashi, Kazuyoshi; Toda, Shuji; Oyama, Jun-ichi; Node, Koichi; Morita, Shigeki (PLOS ONE, 2015)
Background Small caliber vascular prostheses are not clinically available because synthetic vascular prostheses lack endothelial cells which modulate platelet activation, leukocyte adhesion, thrombosis, and the regulation of vasomotor tone by the production of vasoactive substances. We developed a novel method to create scaffold-free tubular tissue from multicellular spheroids (MCS) using a “Bio-3D printer”-based system. This system enables the creation of pre-designed three-dimensional structures using a computer controlled robotics system. With this system, we created a tubular structure and studied its biological features. Methods and Results Using a “Bio-3D printer,” we made scaffold-free tubular tissues (inner diameter of 1.5 mm) from a total of 500 MCSs (2.5× 104 cells per one MCS) composed of human umbilical vein endothelial cells (40%), human aortic smooth muscle cells (10%), and normal human dermal fibroblasts (50%). The tubular tissues were cultured in a perfusion system and implanted into the abdominal aortas of F344 nude rats. We assessed the flow by ultrasonography and performed histological examinations on the second (n = 5) and fifth (n = 5) day after implantation. All grafts were patent and remodeling of the tubular tissues (enlargement of the lumen area and thinning of the wall) was observed. A layer of endothelial cells was confirmed five days after implantation. Conclusions The scaffold-free tubular tissues made of MCS using a Bio-3D printer underwent remodeling and endothelialization. Further studies are warranted to elucidate the underlying mechanism of endothelialization and its function, as well as the long-term results.